Assessment of Utilized Focused Educational Approaches Towards Enhancement of Community Knowledge, Attitudes, and Practices in Solid Waste Management - Rainiel Bryan V Domasian; Ofelia B Maningas; Jamine A Bautista; Jomar P Tañesa; Angelika Ross I Tagum; Francis A Martinez (Inclusive Society and Sustainability Studies, 2025)
This study examines the impact of the "I TEACH-Environmental Protection Project" on the knowledge, attitudes, and practices (KAP) of community members regarding solid waste management. A focused educational approach (FEA) serves as the intervention, which includes interactive seminar workshops, the distribution of educational materials such as tarpaulins and flyers, and active community participation in Clean-Up Drives. A total of 174 participants were selected using a stratified sampling technique, and pre- and post-intervention data were collected through surveys and observational assessments to measure changes in knowledge of waste segregation, policy awareness, and understanding of environmental impact. The seminar focused on key provisions of Republic Act 9003, the Ecological Solid Waste Management Act of 2000, which underscores proper waste management, resource conservation, and community responsibility. Discussions covered the adverse effects of poor waste disposal, the role of local government units, the use of colour-coded bins, and adherence to waste disposal schedules. The intervention emphasized the 5Rs strategy (Reuse, Reduce, Recycle, Repair, Recover) and the establishment of Material Recovery Facilities (MRFs). The results indicated a significant improvement in knowledge and attitudes, with practices showing the most notable progress, particularly in waste segregation, recycling, and proper disposal methods. Participants demonstrated enhanced compliance with waste management policies, including the strict implementation of five-colour bins. The study fills a critical gap in current knowledge by proving that targeted educational initiatives effectively shift KAP towards sustainable waste management. The results underscore the importance of ongoing public education and effective policy enforcement to ensure long-term environmental sustainability.